Experimental Validation of a Hybrid Storage Framework to Cope With Fluctuating Power of Hybrid Renewable Energy-Based Systems - Naderi, Ehsan; K. C., Bibek; Ansari, Meisam; Asrari, Arash (IEEE transactions on energy conversion, 2021)
The technology of supercapacitor is vastly examined by researchers to cope with a lower power density of battery. It is validated that a hybrid battery-supercapacitor storage (HBSS) framework can improve the overall efficiency due to taking advantage of battery's higher energy density and supercapacitor's higher power density. Despite the extensive investigations on this hybrid storage scheme in the electric vehicle (EV) industry, its experimental implementation in the power grid to cope with non-dispatchable nature of wind and solar energy is still in its initial stages. As a result, this paper concentrates on analysis of its experimental implementation on a lab-scale hybrid microgrid located at Southern Illinois University, Carbondale, IL, USA containing two wind turbines and two photovoltaic (PV) modules. The objective of this work is to promote the utilization of the experimentally validated lab-scale HBSS in power industry.